Territorial organization, natural resources and Constituent Assembly in Bolivia: towards a Plurinational State? - Garcés V, Fernando (2016)
The approach of the author makes reference to how territorial ordering and control-state, communal and private-of strategic resources are central themes of debate in Bolivia’s Constituent Assembly. Garcés provides an over view of the proposals of organizations and of Bolivian government and concludes by indicating that it will be a challenge for the Assembly and for the Morales government to take into account the proposals of the indigenous and peasant organizations.